Kajian Literatur Faktor yang Berhubungan dengan Kesehatan Mental Pada Remaja - Fatya Ulya; Noor Alis Setiyadi (Journal of Health and Therapy, 2021)
Background: Adolescents are a transitional period between childhood and adulthood and formulate their identity as adults, where adolescents experience changes that occur in their bodies, dev elop new thoughts and are easily aroused erotically so that they affect adolescent mental health. Purpose: to conduct a literature review from various journals to explain the factors associated with mental health in adolescents. The method used is literature review using two databases, namely Google Scholar and Pubmed using the keywords "mental health", "mental health", "mental health" adolescents, mental health "adolescents," related factors "," related factors ", related factor. Results: A total of 6 journals that have been reviewed explained that there is a significant relationship between online games, religiosity, parenting styles, peer-to-peer environment, Dhuha prayer on mental health in adolescents. Conclusion: Mental health in adolescents is very low, there are various factors so that prevention efforts are needed, especially the family because it is the main means. Suggestions for further researchers can conduct research with multivariate analysis and can examine various other factors related to mental health in adolescents and include complete and clear operational definitions of variables.